After New Labour - Leggett, W. author. aut Link
VIII, 196 p.
Keywords: What's Left after New Labour? This timely book assesses the legacy of both the Third Way and its critics. Analysing the relationship between social theory and political strategy, it outlines the basis of a post-New Labour project. This reconnects with the concerns of the Left, while preserving what was important in the Third Way. Collapsing the boundaries between sociology and political science, this book is essential reading for anyone interested in centre-left renewal.